Detection of cytosine methylation in Burkholderia cenocepacia by single-molecule real-time sequencing and whole-genome bisulfite sequencing. Issue 3 (10th March 2021) - Vandenbussche, Ian; Sass, Andrea; Van Nieuwerburgh, Filip; Pinto-Carbó, Marta; Mannweiler, Olga; Eberl, Leo; Coenye, Tom
Abstract : Research on prokaryotic epigenetics, the study of heritable changes in gene expression independent of sequence changes, led to the identification of DNA methylation as a versatile regulator of diverse cellular processes. Methylation of adenine bases is often linked to regulation of gene expression in bacteria, but cytosine methylation is also frequently observed. In this study, we present a complete overview of the cytosine methylome in Burkholderia cenocepacia, an opportunistic respiratory pathogen in cystic fibrosis patients. Single-molecule real-time (SMRT) sequencing was used to map all 4mC-modified cytosines, as analysis of the predicted MTases in the B. cenocepacia genome revealed the presence of a 4mC-specific phage MTase, M.BceJII, targeting GGC C sequences. Methylation motif GCGGC CGC was identified, and out of 6850 motifs detected across the genome, 2051 (29.9 %) were methylated at the fifth position. Whole-genome bisulfite sequencing (WGBS) was performed to map 5mC methylation and 1635 5mC-modified cytosines were identified in C pG motifs. A comparison of the genomic positions of the modified bases called by each method revealed no overlap, which confirmed the authenticity of the detected 4mC and 5mC methylation by SMRT sequencing and WGBS, respectively. Large inter-strain variation of the 4mC-methylated cytosines was observed when B. cenocepacia strains J2315 and K56-2 were compared, which suggests that GGC C methylation patterns in B. cenocepacia are strain-specific. It seems likely that 4mC methylation of GGC C is not involved in regulation of gene expression but rather is a remnant of bacteriophage invasion, in which methylation of the phage genome was crucial for protection against restriction-modification systems of B. cenocepacia .